2008
DOI: 10.1097/tp.0b013e31816a33d4
|View full text |Cite
|
Sign up to set email alerts
|

Does Reduction in Immunosuppression in Viremic Patients Prevent BK Virus Nephropathy in De Novo Renal Transplant Recipients? A Prospective Study

Abstract: Reduction of IS is probably an effective therapeutic option to clear viremia and prevent BKVN in viremic renal transplant patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
75
2
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(94 citation statements)
references
References 26 publications
16
75
2
1
Order By: Relevance
“…The BK polyomavirus has been proven to be one of the major viral complications in renal allografts [Andrews et al, 1988;Randhawa et al, 1999Randhawa et al, , 2005Hirsch and Steiger, 2003]. At present there is no efficient antiviral therapy available and the treatment of reactivated BKV infection is limited to reducing the immunosuppressive regimen [Almeras et al, 2008;Saad et al, 2008]. In about one-quarter to one-third of kidney transplant (KTx) patients, the virus was found in the urine, about 10-15% of BKV-infected patients reveal viremia and about 5% of BKV-infected patients develop BKVassociated nephropathy [Hirsch et al, 2002;Viscount et al, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…The BK polyomavirus has been proven to be one of the major viral complications in renal allografts [Andrews et al, 1988;Randhawa et al, 1999Randhawa et al, , 2005Hirsch and Steiger, 2003]. At present there is no efficient antiviral therapy available and the treatment of reactivated BKV infection is limited to reducing the immunosuppressive regimen [Almeras et al, 2008;Saad et al, 2008]. In about one-quarter to one-third of kidney transplant (KTx) patients, the virus was found in the urine, about 10-15% of BKV-infected patients reveal viremia and about 5% of BKV-infected patients develop BKVassociated nephropathy [Hirsch et al, 2002;Viscount et al, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…Since PyVAN is preceded by BKV-viruria and viremia (4,5), several groups have used BKV-viremia as a surrogate marker of PyVAN to reduce immunosuppression (6)(7)(8)(9)(10). This preemptive approach has emerged as effective and safe to clear BKV-viremia without functional impairment in most cases (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…In our studies using BKV VP1 mRNA levels, we found the incidence of BKV replication to be 10% at 1 month, 20% at 3 months, 30% at 6 months which plateaued at 12 month post-transplantation. Similarly other studies identified viruria rates of 19% to 49% within the first year post-transplantation using DNA based assays [9,10]. Hirsch and colleagues detected BKV replication using decoy cells in the urine in 30% of their study population [11].…”
Section: Natural History Of Bkv Replicationmentioning
confidence: 99%
“…In another study of 123 patients, 13 developed viremia in which 2 had evidence of BKVN and the remaining 11 did not. With reduction in immunosuppression, 10 of 11 patients without BKVN had clearance of viremia by median of 5 months follow up [10]. Schaub and colleagues evaluated the impact of a three step protocol for reduction in immunosuppression in patients with viremia, presumptive BKVN and biopsy confirmed BKVN.…”
Section: Preemptive Reduction In Immunosuppressive Therapiesmentioning
confidence: 99%